Reward-based reinforcement learning is altered among individuals with a history of major depressive disorder and psychomotor retardation symptoms. (August 2022) - Letkiewicz, Allison M.; Cochran, Amy L.; Mittal, Vijay A.; Walther, Sebastian; Shankman, Stewart A.
Abstract: Reward-based reinforcement learning impairments are common in major depressive disorder, but it is unclear which aspects of reward-based reinforcement learning are disrupted in remitted major depression (rMDD). Given that the neurobiological substrates that implement reward-based RL are also strongly implicated in psychomotor retardation (PmR), the present study sought to test whether reward-based reinforcement learning is altered in rMDD individuals with a history of PmR. Three groups of individuals (1) rMDD with past PmR (PmR+, N = 34), (2) rMDD without past PmR (PmR-, N = 44), and (3) healthy controls (N = 90) completed a reward-based reinforcement learning task. Computational modeling was applied to test for group differences in model-derived parameters – specifically, learning rates and reward sensitivity. Compared to controls, rMDD PmR + exhibited lower learning rates, but not reduced reward sensitivity. By contrast, rMDD PmR- did not significantly differ from controls on either of the model-derived parameters. Follow-up analyses indicated that the results were not due to current psychopathology symptoms. Results indicate that a history of PmR predicts altered reward-based reinforcement learning in rMDD. Abnormal reward-related reinforcement learning may reflect a scar of past depressive episodes that contained psychomotor symptoms, or a trait-like deficit that preceded these episodes.